Evaluación de tres niveles (20,30,40%)de ensilaje en alimentación de terneras girolando mestizo de la etapa de crecimiento en el rancho ganagro en el recinto Recta de Vélez del cantón Pujili - Peñafiel Macias, Juan Carlos (2015)
The research was carried out at the farm Ganagro that belongs to Mr. Reyes. It is located at the Recta de Velez recinto, in the north east of La Maná canton; 10 km. on the way to Latacunga. Three levels of silage T1 20%, T2 30% and T3 40% were evaluated and a control. The obtained results in weight gain per week show statistical significant differences in treatment silage T3 40%, with the greatest registered gain during the research (810 g) d-1. In the total period of intake, there were not statistical differences; the best registered weight was silage T3 40% with (531g) d -1. In the total period of intake, there were not statistical differences, so it showed that the percentage was correct according to the weight of the animal during the research.